Surgical resection combined with perioperative chemotherapy for a patient with locally recurrent, previously stage IV thymic small‐cell carcinoma: A case report. Issue 23 (7th November 2022) - Terada, Junki; Toyoda, Yuko; Takeuchi, Eiji; Tanida, Nobuyuki; Ito, Satoshi; Yorita, Kenji; Matsuoka, Hisashi; Bando, Hiroki; Morita, Yutaka; Okamoto, Yuri; Shinohara, Tsutomu
Abstract: An 83‐year‐old Japanese man visited our hospital with dyspnea and general fatigue. Computed tomography (CT) revealed a tumor in the anterior mediastinum, bilateral pleural effusion, pericardial fluid, and multiple liver nodules. We performed a CT‐guided tumor biopsy, and the patient was diagnosed with thymic small‐cell carcinoma, Masaoka–Koga stage classification IVb. The patient received four cycles of carboplatin and etoposide, and all lesions disappeared on CT. However, after 6 months, CT revealed a recurrent tumor in the anterior mediastinum. After one cycle of rechallenge chemotherapy, we performed extended total thymectomy followed by another three cycles of chemotherapy. More than 2.5 years after the last chemotherapy session, the patient's carcinoma did not recur. Thus, this case suggests that salvage surgery may be a treatment option for local recurrence of thymic carcinoma after complete remission with chemotherapy, even in patients with stage IV cancer. Abstract : We present the case of an elderly man with thymic small‐cell carcinoma, a thymic neuroendocrine tumor, where multidisciplinary treatment, including chemotherapy comprising carboplatin and etoposide, and salvage surgery, was considered effective. Chest computed tomography scans show that 4 months after initiation of chemotherapy, the tumor and pleural effusions had disappeared (second from left). Six months after the confirmed complete response, a recurrent tumor, approximately 2 cm in size, was observed in the anterior mediastinum (third from left, circle). Two and a half years after the end of the treatment, the tumor had not recurred (right). The levels of neuron‐specific enolase (NSE) and pro‐gastrin‐releasing peptide (proGRP), tumor markers of small cell carcinoma, fluctuate with the disease status. Data on the NSE level after 25 months are not available. The orange and blue dotted lines on the graph represent the upper limit of normal for proGRP (80.0 pg/ml) and NSE (12.0 ng/ml), respectively.